2015
DOI: 10.1016/j.scienta.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Seed curvature as a useful marker to transfer morphologic, agronomic, chemical and sensory traits from Ganxet common bean ( Phaseolus vulgaris L.)

Abstract: t r a c tThe Ganxet bean is a highly appreciated landrace characterized by markedly curved seeds, high protein content, low seed-coat perceptibility, and low mealiness. To analyze the genetic control of seed curvature and of morphological, agronomical, chemical, and sensory traits related to high quality in these beans, we used an Additive, Dominance, and Additive × Additive model applied to Ganxet and Faba Asturiana varieties, their F 1 , F 2 , BC 1 P 1 , and BC 1 P 2 progenies. The narrow-sense heritability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
7
1
Order By: Relevance
“…The total protein content of Ganxet beans was calculated as 24.7 ± 0.4% which is in the range -29% previously reported by Rivera et al (2015). Similar protein contents were reported previously for other pulses including faba beans, lentils, and lupins (Boye, Zare, & Pletch, 2010;Lizarazo et al, 2015).…”
Section: Protein Extractionsupporting
confidence: 87%
See 2 more Smart Citations
“…The total protein content of Ganxet beans was calculated as 24.7 ± 0.4% which is in the range -29% previously reported by Rivera et al (2015). Similar protein contents were reported previously for other pulses including faba beans, lentils, and lupins (Boye, Zare, & Pletch, 2010;Lizarazo et al, 2015).…”
Section: Protein Extractionsupporting
confidence: 87%
“…Dry seeds of common beans are excellent protein sources. Indeed their protein content can be up to three fold higher than in cereals (Rivera, Roselló, & Casañas, 2015) and contribute to approximately 6 g of protein per capita and per day in several developing countries (Luna-Vital, Mojica, González de Mejía, Mendoza, & Loarca-Piña, 2015). Ganxet beans (Phaseolus vulgaris L. var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivera and collab. investigated seed curvature in Spanish local Ganxet common beans and concluded that easy to measure seed curvature being under a simple genetic control could be used as a marker to transfer high protein content and mealiness to other cultivars by backcross procedures [RIVERA et al, 2015] .…”
Section: Figure 3 Upgma Dendrogram Of Seed Morphological Traits Of Gmentioning
confidence: 99%
“…Local landraces with proven qualities and rich diversity up to the consumer demands may serve a good starting material in the breeding programs [RIVERA et al, 2015] . In Turkey, local heirloom dry beans have been grown in response to a constant demand by costumers for their quality and seed traits.…”
Section: Introductionmentioning
confidence: 99%